KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA AKADEMIK GURU PADA SMA N 11 MUARO JAMBI - Muspawi, Mohammad; Panjaitan, Keiza; Silalahi, Nova Ida; Selviana, Selviana (Universitas Riau, 2023)
As a school principal, the leader plays an active role and is always influential in all matters relating to the needs of school staff, teachers and all students. A good school principal has the task of fostering school culture and discipline, being a work partner, creating cooperation between all school students to create a friendly and goal-oriented school environment. The purpose of this research is to determine the role of school principals as leaders in building teacher academic culture. The leadership of the school principal certainly plays an important role in shaping and creating the teacher's academic culture. A good academic culture should ideally be possessed by all teachers in a school. This article discusses methods, obstacles and how school leaders overcome obstacles in building a teacher's academic culture.